Peran Fintech Dalam Meningkatkan Akses Keuangan Di Era Digital : Studi Literatur - Zulfa Qur’anisa; Mira Herawati; Lisvi Lisvi; Melinda Helmalia Putri; O. Feriyanto (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
Financial Technology (FinTech) is an innovation in financial services that uses digital technology to provide easier, more efficient, and affordable access. This article discusses the development of FinTech in Indonesia, including its role in increasing financial inclusion, providing digital banking services, electronic payments, and peer-to-peer lending business models. Through literature analysis, this article shows that FinTech has driven significant changes in financial access and interaction, especially for those in remote areas or do not have access to traditional financial services. Although FinTech offers many advantages, such as efficiency and ease of transactions, challenges such as limited access to technology and security risks still need to be addressed. Adaptive regulation and collaboration with traditional financial institutions are needed to maximize FinTech's potential in supporting financial inclusion and sustainable economic development in Indonesia.